The maternal health of American Indian and Alaska Native people: A scoping review. (January 2023) - Burns, Ailish; DeAtley, Teresa; Short, Susan E.
Abstract: Indigenous people in the United States experience disadvantage in multiple domains of health. Yet, their maternal health receives limited research attention. With a focus on empirical research findings, we conduct a scoping review to address two questions: 1) what does the literature tell us about the patterns and prevalence of maternal mortality and morbidity of American Indian and Alaska Native (AI/AN) people? and 2) how do existing studies explain these patterns? A search of CINAHL, Embase and Medline yielded 4757 English-language articles, with 66 eligible for close review. Of these, few focused specifically on AI/AN people's maternal health. AI/AN people experience higher levels of maternal mortality and morbidity than non-Hispanic White people, with estimates that vary substantially across samples and geography. Explanations for the maternal health of AI/AN people focused on individual factors such as poverty, cultural beliefs, and access to healthcare (e.g. lack of insurance). Studies rarely addressed the varied historical and structural contexts of AI/AN tribal nations, such as harms associated with colonization and economic marginalization. Research for and by Indigenous communities and nations is needed to redress the effective erasure of AI/AN people's maternal health experiences and to advance solutions that will promote their health and well-being. Highlights: The maternal health of AI/AN people is understudied. AI/AN people have high rates of maternal mortality and severe maternal morbidity. Most studies focused on individual-level predictors of maternal health outcomes. Few studies examined the structural or historical determinants of maternal health. More research should pay attention to the harmful legacies of colonization.